Association of Native American ancestry and common variants in ACE, ADIPOR2, MTNR1B, GCK, TCF7L2 and FTO genes with glycemic traits in Colombian population (2018)
Insulin resistance and defects in other related glycemic traits are common findings in the context of Metabolic Syndrome. Although genetic factors are clearly implied in susceptibility, and some gene variants have been identified mainly in populations of European ancestry, little is known about this aspect in admixed populations. The association of insulin resistance, β-cell function, fasting insulin and glucose levels with 48 gene variants, previously related to metabolic syndrome components, and with the ancestral genetic composition, estimated on 50 ancestry informative markers, was evaluated in 417 individuals from the Colombian admixed population. The Native American genetic ancestry was associated with a low β-cell function (odds ratio (OR) of 1.73 and 95% confidence interval (95% CI) of 1.07–2.81, p = 0.026). Significant genotypic associations were obtained (q-value < 0.05) for gene variants in ACE (rs4340; OR (95% CI): 2.79 (1.58–4.91), insulin resistance; mean difference (95% CI): 0.273 (0.141; 0.406), fasting insulin), ADIPOR2 (rs11061971; OR (95% CI): 0.14 (0.04–0.48), low β-cell function), MTNR1B (rs10830963; mean difference (95% CI): 0.032 (0.013; 0.051), fasting glucose) and GCK (rs4607517; mean difference (95% CI): 0.038 (0.020;0.056) and rs1799884; mean difference (95% CI): 0.027 (0.013–0.041), fasting glucose). Also the well-known gene variants rs7903146 in TCF7L2, and rs17817449 in FTO, were nominally associated with hyperglycemia (rs7903146), as well as with higher fasting insulin levels (rs17817449). Our findings indicate that gene variants in ACE, ADIPOR2, MTNR1B, GCK, TCF7L2 and FTO, are associated with glycemic traits in the admixed Colombian population, while a higher Native American genetic component is related to lower β-cell function.